Apomorphine sublingual film for off episodes in Parkinson's disease: a randomised, double-blind, placebo-controlled phase 3 study. Issue 2 (February 2020) - Olanow, C Warren; Factor, Stewart A; Espay, Alberto J; Hauser, Robert A; Shill, Holly A; Isaacson, Stuart; Pahwa, Rajesh; Leinonen, Mika; Bhargava, Parul; Sciarappa, Ken; Navia, Bradford; Blum, David; et al.
Summary: Background: Many patients with Parkinson's disease have potentially disabling off episodes that are not predictably responsive to levodopa. In this study, we assessed the safety and efficacy of apomorphine sublingual film as an on-demand therapy for off episodes in patients with Parkinson's disease. Methods: This randomised, double-blind, placebo-controlled study was done by movement disorder specialists at 32 sites in the USA and one in Canada. Patients with Parkinson's disease who had 2 h or more of off time per day with predictable morning off periods, were responsive to levodopa, and were on stable doses of anti-parkinsonian medication were eligible. In an open-label titration phase, increasing doses of apomorphine sublingual film (10–35 mg) were administered until a tolerable full on response was achieved. Patients were then randomly assigned (1:1) with an interactive web-response system to receive the effective dose of apomorphine sublingual film or matching placebo in a 12-week, double-blind maintenance phase. Randomisation was not stratified, and the block size was four. All patients and study personnel were masked to treatment assignments. The primary endpoint was the in-clinic change from predose to 30 min post-dose in the Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part 3 (motor) score at week 12, analysed on a modified intention-to-treat population by use of a mixed-effect model for repeated measures. Safety analyses were done on all enrolled patients who received at least one dose of study medication. This trial is registered with ClinicalTrials.gov, NCT02469090 . Findings: Between June 18, 2015, and Dec 11, 2017, 109 patients were enrolled and randomly assigned to receive apomorphine sublingual film (n=54) or placebo (n=55). All patients received the assigned study treatment, and 34 (63%) of 54 patients receiving apomorphine sublingual film and 46 (84%) of 55 receiving placebo completed the study. Least squares mean (SE) change from predose to 30 min post-dose in MDS-UPDRS part 3 score at week 12 was −11·1 (SE 1·46, 95% CI −14·0 to −8·2) with apomorphine sublingual film and −3·5 (1·29, −6·1 to −0·9) with placebo (difference −7·6, SE 1·96, 95% CI −11·5 to −3·7; p=0·0002). Mild-to-moderate oropharyngeal events were the most common side-effect, reported in 17 (31%) of 54 patients receiving apomorphine sublingual film and in four (7%) of 55 patients receiving placebo, leading to treatment discontinuation in nine (17%) patients treated with apomorphine and in one (2%) patient treated with placebo. Other treatment-emergent adverse events were transient nausea (in 15 [28%] patients receiving apomorphine sublingual film), somnolence (seven [13%]), and dizziness (five [9%]). Orthostatic hypotension, syncope, dyskinesia, hallucinations, prolongation of the QT interval, and impulse control disorders were infrequent (prevalence ≤2% of all patients) or did not occur. One patient treated with apomorphine sublingual film (with known cardiac risk factors) had a fatal cardiac arrest. Interpretation: Although nearly a third of patients discontinued treatment primarily because of oropharyngeal side-effects, apomorphine sublingual film provided an efficacious, on-demand treatment for off episodes for most patients with Parkinson's disease in this trial. The long-term safety and efficacy of apomorphine sublingual film are currently being investigated. Funding: Cynapsus Therapeutics and Sunovion.